2022
DOI: 10.1111/manc.12402
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional presenteeism: Effects of physical and mental health on work performance

Abstract: Poor health in the workforce is costly to employers and the economy. This is partly due to health problems causing people to spend less time at work but is also due to people being less productive while at work. In this paper, we investigate the causes of dysfunctional presenteeism, defined as reduced productivity at work due to health problems. We find that both physical and mental health significantly predict the probability of dysfunctional presenteeism, and the effects of mental health problems seem to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
1
10
0
1
Order By: Relevance
“…According to the authors, initiatives that limit and help workers manage job stress seem to be the most promising avenue for improving workers' productivity. Furthermore, the authors found that presenteeism rates among workers with poor mental health were relatively insensitive to work environments, in line with other research from the UK [76]; consequently, they suggested that developing institutional arrangements that specifically target the productivity of those experiencing mental ill health may prove challenging. These findings are particularly important in the context of the COVID-19 pandemic due to changes in work arrangements and workplaces (e.g., working from home while trying to balance work with home and care responsibilities, hybrid working arrangements, and ensuring workplaces have COVID-19-secure measures in place).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…According to the authors, initiatives that limit and help workers manage job stress seem to be the most promising avenue for improving workers' productivity. Furthermore, the authors found that presenteeism rates among workers with poor mental health were relatively insensitive to work environments, in line with other research from the UK [76]; consequently, they suggested that developing institutional arrangements that specifically target the productivity of those experiencing mental ill health may prove challenging. These findings are particularly important in the context of the COVID-19 pandemic due to changes in work arrangements and workplaces (e.g., working from home while trying to balance work with home and care responsibilities, hybrid working arrangements, and ensuring workplaces have COVID-19-secure measures in place).…”
Section: Discussionsupporting
confidence: 72%
“…There is also a need to better understand the extent to which mental illness decreases productivity at work and the mechanisms through which this occurs, as this could help inform the role of employment policy and practices to minimise presenteeism [25]. Some research suggests that conducive working conditions, such as part-time employment and having autonomy over work tasks, can help mitigate the negative impact of mental health on presenteeism [76]. Alongside this, it is important to learn more about the dynamics of the relationship between mental illness and worker productivity to understand the trade-offs between presenteeism and absenteeism [25].…”
Section: Discussionmentioning
confidence: 99%
“…The first asks the number of days the respondent was unable to work, study, or carry out day‐to‐day activities because of feelings in the last 4 weeks (distress‐related work loss days), and the second asks the number of days they cut down on work, study, or day‐to‐day activities as a result of feelings in the last 4 weeks (distress‐related work cutback days). In line with previous research, 1,15 given this analysis is restricted to employed persons these days are assumed to impact on work for this population.…”
Section: Methodsmentioning
confidence: 96%
“…The scores range from 10 to 50. The K10 score was categorized as low (10)(11)(12)(13)(14)(15), moderate (16)(17)(18)(19)(20)(21), high (22)(23)(24)(25)(26)(27)(28)(29), and very-high , in accordance with ABS category parameters. 11 A high K10 score is highly associated with the presence of an anxiety and/or affective disorder and is a commonly used component of international health surveys.…”
Section: Psychological Distressmentioning
confidence: 99%
“…Mental disorders can have significant consequences, not only on the individual level, but also on a societal and economic level. In the context of the workplace,1 2 poor mental health has been linked with absenteeism and presenteeism3–5 leading to decreased workplace performance, productivity and increased risk of unemployment 6 7. Depression and anxiety are the two most common mental disorders globally, and are therefore also most likely to impact work performance and productivity 8…”
Section: Introductionmentioning
confidence: 99%